Comorbidity as an Independent Risk Factor in Patients With Cancer: An 8-Year Population-Based Study. (March 2015) - Chen, Chang-I; Kuan, Ching-Feng; Miser, James; Fang, Yu-Ann; Lam, Carlos; Chiu, Wen-Ta; Li, Yu-Chuan
This study determined the prevalence of medical conditions in patients with cancer and their impact on outcome. We evaluated a cohort of 37 411 patients diagnosed with cancer between 2000 and 2008 in Taiwan, collecting the cancer diagnosis and chronic disease diagnoses. The severity of the comorbid condition was correlated with the cancer diagnosis and outcome. Overall, 71.9% of the study population had 1 or more comorbid conditions. Patients with none (n = 10 508), 1 (n = 8881), 2 (n = 6583), and 3 or more (n = 11 439) comorbid conditions had mortality rates of 11.49%, 15.99%, 19.61%, and 29.39%, respectively. Older patients with comorbid conditions had a significantly higher chance of death. Dementia, heart disease, or cerebrovascular diseases were associated with the highest mortality. Cancer patients with comorbid conditions have a significantly higher risk of death. Prevention and better medical management of comorbid conditions is likely to result in improved outcomes for patients with cancer.